2018
DOI: 10.1007/s12010-018-2810-7
|View full text |Cite
|
Sign up to set email alerts
|

A Tropical Composting Operation Unit at São Paulo Zoo as a Source of Bacterial Proteolytic Enzymes

Abstract: Composting operation systems are valuable sources of microorganisms and enzymes. This work reports the assessment of proteolytic enzymes from cultivable bacteria isolated from a composting facility of the São Paulo Zoo Park (SPZPF), São Paulo, Brazil. Three hundred bacterial isolates were obtained and identified based on 16S rRNA gene as belonging to 13 different genera. The most common genus among the isolates was Bacillus (67%); some of which show high proteolytic activity in their culture media. Biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
0
6
0
5
Order By: Relevance
“…Protease plays an important role in the hydrolysis catalyzation to produce NH 3 (Ros et al 2006). Previous studies detected the thermostability of proteolytic activity in composting leachate, showing that the proteolytic activity was almost unaffected when the temperature was up to 60°C, but it was reduced to 50% while the temperature was above 65°C (Ramos et al 2019). In this study, the temperature was no more than 60°C in the thermophilic stage for TC, whereas the temperature was over 65°C and continued for a relatively long incubation period (10 days) in the same stage of HPC.…”
Section: Disscussionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protease plays an important role in the hydrolysis catalyzation to produce NH 3 (Ros et al 2006). Previous studies detected the thermostability of proteolytic activity in composting leachate, showing that the proteolytic activity was almost unaffected when the temperature was up to 60°C, but it was reduced to 50% while the temperature was above 65°C (Ramos et al 2019). In this study, the temperature was no more than 60°C in the thermophilic stage for TC, whereas the temperature was over 65°C and continued for a relatively long incubation period (10 days) in the same stage of HPC.…”
Section: Disscussionsmentioning
confidence: 99%
“…For example, Sakurai et al (2007) studied the diversity of npr after the application of organic and inorganic fertilizer and they postulated that the proteolytic bacterial community composition may primarily contribute to control the overall soil protease activity. In the composting system, serine-and metalloproteases are the main proteolytic enzymes that secreted by Bacillus isolates (Ramos et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…During the composting of poultry manure, organic N mineralization occurs through a stepwise process including proteolysis, ammonification, and nitrification, which are primarily carried-out by microbial-derived extracellular enzymes (Ouyang and Norton 2020 ). Among these processes, proteolysis is considered the rate-limiting step in the ammonification process, as the protease is required to hydrolyze proteins into amino acids and subsequently metabolize resulting in NH 3 volatilization and the release of NH 4 + in the composts (Swelum et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sakurai et al ( 2007 ) studied the diversity of npr after application of organic and inorganic fertilizer and they postulated that the proteolytic bacterial community composition may primarily contribute to control the overall soil protease activity. In the composting system, serine- and metalloproteases are the main proteolytic enzymes that are secreted by Bacillus isolates (Ramos et al 2019 ). However, the knowledge in the dynamics of proteolytic bacteria is insufficient in the compost systems.…”
Section: Introductionmentioning
confidence: 99%
“…Another study re-inoculated a combination of compost leachate with a nutrient solution in compost piles in order to accelerate the composting process and this was more effective due to the presence of microorganisms with a high capacity for degradation [26]. Furthermore, it has been reported that some strains, like Bacillus spp., that were isolated from a composting plant have proteolytic enzymes which can be used for industrial functions [27].…”
Section: Introductionmentioning
confidence: 99%